Use of waste glass powder in improving the properties of expansive clay soils - J.B., Niyomukiza; A., Eisazadeh; J., Akamumpa; M., Kiwanuka; A., Lukwago; P., Tiboti (Global NEST Journal, 2023)
Expansive soils pose a danger to the foundations of engineering structures due to their poor engineering properties. These soils are usually treated using mechanical techniques, and chemical stabilizers. However, the production of these chemicals is not friendly to the environment, thus a need to adopt waste materials. Therefore, this research investigated the efficacy of utilizing waste crushed glass to alter the engineering properties of the soil. The study's objectives were achieved by conducting experiments on non-stabilized soil, and waste glass powder (WGP) stabilized soil in the percentages of 3, 5, 7, and 9% of dry weight of the soil. The findings showed that adding glass powder to subgrade soil strengthens it and reduces its susceptibility to volume change. The highest compressive strength was obtained after mixing 7% waste glass powder with the soil, and beyond that, the strength reduced. The study found that the inclusion of 7% waste glass powder content is suitable for the stabilization of the soil possessing properties similar to the ones in the study area
Keywords: Clay soil; Environmental conservation; Soil stabilization; Waste glass powder; Waste management